Peran Guru sebagai Motivator dalam Pendidikan Qur’ani: Studi Analisis Tafsir Al-Baghawi - Siti Juariah Juju; Enjang Burhanudin Yusuf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The contemporary decline in learning motivation demands a pedagogical approach that is more humanistic and spiritually grounded. In Islamic education, teachers function not only as transmitters of knowledge but also as motivators who foster students’ intellectual, moral, and spiritual growth. This study analyzes the teacher’s role as a motivator in Qur’anic education based on Al-Baghawi’s Ma‘ālim at-Tanzīl. Using qualitative library research and a thematic tafsir approach, the study examines Qur’anic verses related to motivation, wisdom, exemplary behavior, and character formation. The findings show that Qur’anic motivation in Al-Baghawi’s view is rooted in four core values: rahmah (compassion), hikmah (wisdom), ṣabr (patience), and uswah (exemplary conduct). Compassion builds emotional connection between teachers and students; wisdom guides the contextual selection of teaching methods; patience emphasizes continuous guidance; while exemplary conduct strengthens the internalization of moral values. These principles are highly compatible with modern motivational theories and offer a holistic pedagogical framework suitable for 21st-century education, including digital learning environments. The study concludes that Qur’anic education provides an integrated model that harmonizes academic achievement with character development.